Towards a more analytic expression of grammatical relationships: The use of prepositions and adverbs in early English correspondence - Rutkowska, Hanna (Wydawnictwo Naukowe UAM, 2002)
The focus of my paper is syntactic. It analyses different functions and positions of uninflected words, more precisely prepositions and adverbs, in the fifteenth-century correspondence. The Cely Letters (1472-88) constitute the basis for the analysis, but some examples are also drawn from the letters of the Paston and Plumpton families.
Keywords: przyimki; prepositions; przysłówki; adverbs; korespondencja rodziny Cely; Cely Letters; składnia; syntax